Innovative Model Development Performance Management for Increase Productivity in the Digital Era at PT. Indofood CBP Sukses Makmur Tanah Laut South Kalimantan - Lusiana, Herlina; Azahraty, Azahraty; Ambarwati, Riris (PT Inovasi Pratama Internasional, 2024)
This research is very in-depth and focuses on developing innovative performance management models to increase productivity in the digital era at PT. Indofood CBP Sukses Makmur, Tanah Laut, South Kalimantan. Explanation of the research, in the context of the digital era, and the research methodology used, including the literature study method chosen to gain an in-depth understanding of this research topic. The attached literature review provides a good overview of key concepts relevant to performance management in the digital era. This research has included important theories and findings that support the theoretical basis of the research. The research results highlight the development of innovative performance management models relevant to the digital era, with an emphasis on performance optimization through digital technology, data analytics and efficient improvement processes. Implementation of the model in an organizational context, including specific steps such as goal setting and communication, is an important element in turning the model into concrete action. In addition, the solutions offered to overcome challenges and obstacles that may arise during implementation are wise steps. It reflects a solution-oriented approach and is ready to face changes that may occur on the way to more innovative performance management. This article also demonstrates an understanding of the importance of employee satisfaction, ongoing training, and a focus on results in the context of more adaptive performance management. Thus, this research appears to be a valuable resource for management practitioners, organizational leaders, and researchers interested in understanding and implementing effective performance management in the digital era. Congratulations on your efforts in conducting relevant research and contributing positively to the development of innovative performance management models.